Influence of prenatal hexachlorobenzene, PCB and selenium levels on growth trajectories in the first year of life: Findings from the NEHO birth cohort - Ilaria Cosentini; Silvia Ruggieri; Paolo Colombo; Fabrizio Bianchi; Liliana Cori; Melania Casella; Elisa Eleonora Tavormina; Fabio Cibella; Gaspare Drago (Environment International)
Prenatal exposure to endocrine-disrupting chemicals (EDCs) may impact postnatal growth trajectories, increasing the risk of various diseases later in life. This issue is of particular concern in industrially contaminated areas, where environmental matrices contain mixtures of pollutants. This study aimed to evaluate the associations between cord serum concentrations of organochlorine pollutants (hexachlorobenzene-HCB and polychlorinated biphenyls-PCBs) and essential elements (EEs), and weight growth trajectories during the first year of life. We analyzed data from 237 infants enrolled in the Neonatal Environment and Health Outcomes (NEHO) cohort. Using the Group-Based Multivariate Trajectory modeling approach, we identified three distinct growth trajectories from birth to 12 months, classified as “Higher,” “Normal,” and “Lower.” Multinomial regression models were then applied to the whole sample and stratified by sex to assess the associations between individual exposures and the identified child growth trajectories. HCB exposure was associated with an increased risk of reduced growth during the first year of life in both the overall sample and among males [higher vs normal: ORMale = 0.33 (95 % CIMale:0.12;0.87); lower vs normal: ORMale = 2.17 (95 % CIMale:0.94;5.00)]. Conversely, PCB-180 exposure was linked to higher growth only in females [higher vs normal: ORFemale = 24.10 (95 % CIFemale:1.33;438.24)]. Elevated levels of selenium in cord serum were negatively associated with excessive growth [higher vs normal: OROverall = 0.50 (95 % CIOverall: 0.26;0.97)]. These findings suggest sex-specific effects on the growth profile during the first year of life, with different chemical exposures contributing to different outcomes.